Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1046/j.1464-410x.1997.22624.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor (EGF) and EGF receptor in hypospadias

Abstract: Objective To determine whether alterations in epidermalResults The median EGF density in foreskins obtained by circumcision was 75% (mean 73, se 2.1) compared growth factor (EGF), which plays a major role both in the masculinization of the genitourinary tract and in with 54% (mean 52, se 3.9) for tissue samples from patients with hypospadias (P<0.001); the mean EGFR wound healing, or EGF receptor (EGFR) expression are associated with hypospadias.was similar in both materials. Conclusion The mean EGF value was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 3 publications
2
13
0
2
Order By: Relevance
“…Surgical technique is thought to be a key factor, although a local deficit in growth factors may also play a role [16]. Local or systemic, adjuvant or neoadjuvant hormonal therapy has been proposed to reduce fistula development, but the results are controversial so far.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical technique is thought to be a key factor, although a local deficit in growth factors may also play a role [16]. Local or systemic, adjuvant or neoadjuvant hormonal therapy has been proposed to reduce fistula development, but the results are controversial so far.…”
Section: Discussionmentioning
confidence: 99%
“…The authors tried to explain the postoperative edema, poor wound healing leading to urethrocutaneous fistulae, and increased analgesia requirements in patients undergoing hypospadias surgery in terms of differences in tissue environment [6]. In a previous study, El-Galley et al [8] showed that mean epidermal growth factor was decreased in skin adjacent to hypospadias defects compared to normal phallic skin, and suggested that this may be related to the etiology of hypospadias and to possible wound complications postoperatively. The arterial blood supply of the hypospadiac prepuce is different than normal [3].…”
Section: Discussionmentioning
confidence: 99%
“…Full differentiation, however, requires the presence of testosterone (63), similar to the role of EGF to promote growth and differentiation of the mouse uterus and vagina (65). Reduced EGF density in foreskins was discovered in 16 children undergoing hypospadias surgery compared with 22 children undergoing circumcision (p = 0.001), although there was no reduction in mean EGF receptors (EGFR) (66). This suggests interference with receptor binding.…”
Section: Etiologymentioning
confidence: 99%